Evolution of shallow post-bog soils developed on Holocene carbonate sediments in NW Poland - Grzegorz Jarnuszewski; Edward Meller; Teodor Kitczak (Journal of Water and Land Development, 2023)
This research presents the characteristics and inferred evolution of post-bog soils developed in the Last Glacial Maximum area of northwestern Poland near the southern Baltic coast. The study involved a total of five sites near existing lakes in NW Poland. In total, 21 soil pits were described and sampled and 17 piezometers were installed. In soil samples chemical and physical properties were determined. During the hydrological year the water level was checked and chemical properties of water were determined, the floristic composition at each location was also carried out. Mineralisation of post-bog soils initiated by dehydration leads to the decomposition of organic surface layers and an increase in CaCO3 content as well as mineral non-lime components at the expense of organic matter. A sequence of five soil types occurs in this landscape: Sapric Histosols (Limnic), Drainic Histosols (Calcaric, Limnic), Histic Gleysols (Murshic), Umbric Gleysols (Hyperhumic), Gleyic Phaeozems (Hyperhumic) that represent individual stages of soil genesis. Differences between the chemical properties of soils are apparent between organic vs organic-mineral and mineral layers. Man-induced drainage of post-bog soils changes their physical parameters. Bulk density increase and water retention decrease. The fluctuation of groundwater determines the moisture content of post-bog soils and affects the species composition of vegetation. Chemistry of groundwater is shaped mainly by the construction of catchment and the nature of its use, however, it is modified as a result of the inflow of macronutrients released during organic matter mineralisation processes and leaching of exchangeable forms from the sorption complex.